Fatigue behaviour of AA6061-T6 alloys in the corrosive environment - Li, Peifeng (2018)
The combined effects of corrosion and fatigue are known to be hazardous threats to structural integrity of aluminium alloys that are being extensively used in marine applications. This work investigated the fatigue crack initiation and growth behaviour of AA6061-T6 alloys in 3.5 wt% NaCl simulated seawater using scanning electron microscope and electron backscatter diffraction characterisation techniques. It was found that the fatigue resistance of AA6061-T6 is drastically downgraded when subjected to the corrosive environment of 3.5 wt% NaCl solution. High stress concentration at both sides of a pit mouth in conjunction with attacked grain boundaries facilitates fatigue crack nucleation, while the presence of hydrogen formed by corrosion reactions causes crack tip embrittlement and thus increases crack growth rate. Fractographic analysis reveals that there is a change in fatigue crack growth mechanism of AA6061-T6 alloys tested in the NaCl solution. At short crack length, the crack develops transgranularly along crystallographic planes due to hydrogen-enhanced decohesion process. Further crack growth is dominated by adsorption induced dislocation emission process, resulting in the mixed mode of intergranular and transgranular crack growth.